2009
DOI: 10.1002/pi.2627
|View full text |Cite
|
Sign up to set email alerts
|

Study of dual responsive poly[(maleilated dextran)‐graft‐(N‐isopropylacrylamide)] hydrogel nanoparticles: preparation, characterization and biological evaluation

et al.

Abstract: BACKGROUND: Much interest has recently been shown in fundamental studies and technological developments of polymeric nanoparticles. Novel dual temperature‐ and pH‐sensitive stabilized nanoparticles composed of maleilated dextran (Dex‐MA) and N‐isopropylacrylamide (NIPAAm) were prepared and investigated to be used for the controlled release of 10‐hydroxycamptothecin. RESULTS: The resultant nanoparticles showed spherical geometry, with diameters ranging from 60 to 300 nm, the variation achieved by adjusting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
1
5
0
1
Order By: Relevance
“…Because of the protons of hydroxyl groups, the characteristic peaks of DOX at 13.1 and 14.0 ppm were present in the spectra of M.LNT‐ DOX and FA‐M.LNT‐DOX (Figure (c) and (d)) . The presence of several peaks at 6.5–9.0 ppm (Figure (d)), which could be assigned to the aromatic protons of FA according to the reported literature, confirmed the existence of the FA moiety in FA‐M.LNT‐DOX conjugate. Thus it could be concluded that the FA‐M.LNT‐DOX conjugate was successfully synthesized by this protocol.…”
Section: Resultssupporting
confidence: 74%
“…Because of the protons of hydroxyl groups, the characteristic peaks of DOX at 13.1 and 14.0 ppm were present in the spectra of M.LNT‐ DOX and FA‐M.LNT‐DOX (Figure (c) and (d)) . The presence of several peaks at 6.5–9.0 ppm (Figure (d)), which could be assigned to the aromatic protons of FA according to the reported literature, confirmed the existence of the FA moiety in FA‐M.LNT‐DOX conjugate. Thus it could be concluded that the FA‐M.LNT‐DOX conjugate was successfully synthesized by this protocol.…”
Section: Resultssupporting
confidence: 74%
“…Related to the synthesis of dextran-based thermo-responsive nanogels, only two works have been published. 31,32 In both of them, nanogels were prepared by emulsion polymerization using NIPAM as a temperature-sensitive monomer and maleilated dextran or Dex-lactateHEMA as cross-linkers.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, much attention has been paid to the polysaccharide‐based hydrogels as drug carriers owing to their low toxicity, biocompatibility and renewability . However, some hydrogels prepared from single polysaccharide such as starch, dextran and agarose are nonresponsive to external stimuli like pH and temperature, which is considered to be a limitation in their applications as drug carriers . To address this drawback, efforts have been made to fabricate chemically modified polysaccharide‐based hydrogels by grafting.…”
Section: Introductionmentioning
confidence: 99%
“…[5] However, some hydrogels prepared from singlep olysaccharide such as starch, dextran and agarose are nonresponsive to external stimuli like pH and temperature, which is considered to be a limitation in their applications as drug carriers. [6] To address this drawback, efforts have been made to fabricatec hemically modified polysaccharide-based hydrogels by grafting. Graft copolymerization of vinyl monomers, such as N,N-diethylacrylamide, methacrylic acida nd 2-acrylamido-2-methyl-1-propanesulfonica cid, onto polysaccharide is an efficient approach to improvet he inherentp roperties of polysaccharides.…”
Section: Introductionmentioning
confidence: 99%